2001
DOI: 10.1046/j.1365-2893.2001.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin treatment in dialysis patients with chronic hepatitis C virus infection – a pilot study

Abstract: Standard treatment for chronic hepatitis C is with interferon (IFN)-alpha and ribavirin for 6-12 months. In dialysis patients only interferon therapy is currently used due to the lack of knowledge concerning ribavirin dosage and side-effects. The aim of this study was to investigate if ribavirin can be added to interferon when treating dialysis patients with hepatitis C. Five patients on haemodialysis and one patient on peritoneal dialysis with chronic hepatitis C, five with genotype 1 and one with genotype 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 23 publications
4
100
0
4
Order By: Relevance
“…Nevertheless, attempts have been made to use low doses of ribavirin (200 mg daily or every other day) with interferon therapy in patients on dialysis, but anemia was still problematic and required intensive monitoring and erythropoietin therapy. 48 Studies of peginterferon therapy are currently under way in patients with varying degrees of renal insufficiency. Until there is more information on the safety and efficacy of peginterferon with or without ribavirin in patients with renal disease, these agents should be used with caution by investigators with experience in managing interferon side effects and preferably in the context of prospective trials.…”
Section: Treatment Of Hepatitis C In Understudied Populationsmentioning
confidence: 99%
“…Nevertheless, attempts have been made to use low doses of ribavirin (200 mg daily or every other day) with interferon therapy in patients on dialysis, but anemia was still problematic and required intensive monitoring and erythropoietin therapy. 48 Studies of peginterferon therapy are currently under way in patients with varying degrees of renal insufficiency. Until there is more information on the safety and efficacy of peginterferon with or without ribavirin in patients with renal disease, these agents should be used with caution by investigators with experience in managing interferon side effects and preferably in the context of prospective trials.…”
Section: Treatment Of Hepatitis C In Understudied Populationsmentioning
confidence: 99%
“…This trial has demonstrated that, despite the impaired clearance of ribavirin in patients with renal dysfunction, the drug could still be used safely if its dose is reduced and if its plasma concentrations and hemoglobin levels are closely monitored (69). Treatment with ribavirin alone has failed to clear HCV RNA in renal transplant recipients, but has been found to cause a drop in HCV RNA titers by 70-82% in 57% of the patients, and has not been associated with any detrimental side-effects on graft function (70).…”
Section: Management Of Hcv In Renal Transplant Patientsmentioning
confidence: 99%
“…Data on alternative therapeutic options, such as combination therapy with ribavirin, are even more preliminary in nature. [55][56][57] The optimal regimen for interferon monotherapy in dialysis patients with chronic hepatitis C remains poorly established. The primary goal of our study was to synthesize the available evidence on the tolerability and efficacy of initial interferon monotherapy in dialysis patients with chronic hepatitis C by performing a systematic review of the literature with a meta-analysis of clinical trials.…”
Section: Introductionmentioning
confidence: 99%